STRATEGI PENGEMBANGAN SULAM BAYANG - Marlius, Doni; Putra, Rino Dwi (LLDIKTI Wilayah X, 2018)
This research was conducted using descriptive method to analyze and interpret the condition or condition of shadow embroidery industry barung barung balantai so that policy can be taken. The result of this research is shadow embroidery artisans must maximize social media for promotion, improve good relationship with local government in the form of continuous cooperation in order to maximize the existing potential in the shadow embroidery, utilize existing skilled manpower to do the coaching on the craftsmen so that the amount increases to increase production capacity and there is cutting time in the work, cooperating with other industries that support shadow embroidery such as bags, shoes, etc. through local government, making a joint container or a kind of shadow embroidery union can be a cooperative institution, marketing institutions or other institutions, increasing skill of craftsmen in processing materials embroidery and skill from the owner in managing his group facing competition with other products, as well as increasing the use of technology in the design and development of motives.Penelitian ini dilakukan menggunakan metode deskriptif untuk menganalisis dan menginterprestasikan keadaan atau kondisi industri sulam bayangan barung barung balantai sehingga dapat diambil kebijakan. Hasil penelitian ini pengrajin sulam bayangan harus memaksimalkan media sosial untuk promosi, meningkatkan hubungan baik dengan pemerintah daerah berupa kerjasama yang kontinue guna memaksimalkan potensi yang ada pada sulam bayangan, memanfaatkan tenaga terampil yang ada untuk melakukan pembinaan pada pengrajin sehingga jumlahnya bertambah agar kapasitas produksi meningkat dan ada pemangkasan waktu dalam pengerjaan, menjalin kerjasama dengan industri lain yang mendukung sulam bayangan seperti tas, sepatu, dll melalui pemerintah daerah, membuat wadah bersama atau semacam persatuan sulam bayangan bisa berupa lembaga koperasi, lembaga pemasaran ataupun lembaga lainnya, meningkatkan skill pengrajin dalam mengolah bahan sulam dan skill dari pemilik dalam mengelola kelompoknya menghadapi persaingan dengan produk lain, serta meningkatkan penggunaan teknologi dalam desain dan pengembangan motif.